Nitrogen assimilation and photorespiration become more efficient under chloride nutrition as a beneficial macronutrient - Peinado-Torrubia, Procopio; Álvarez, Rosario; Lucas, Marta; Franco-Navarro, Juan D.; Durán-Gutiérrez, Francisco J.; Colmenero-Flores, José M.; Rosales, Miguel A. (Frontiers in Plant Science, 2023)
Chloride (Cl−) and nitrate (NO3−) are closely related anions involved in plant growth. Their similar physical and chemical properties make them to interact in cellular processes like electrical balance and osmoregulation. Since both anions share transport mechanisms, Cl− has been considered to antagonize NO3− uptake and accumulation in plants. However, we have recently demonstrated that Cl− provided at beneficial macronutrient levels improves nitrogen (N) use efficiency (NUE). Biochemical mechanisms by which beneficial Cl− nutrition improves NUE in plants are poorly understood. First, we determined that Cl− nutrition at beneficial macronutrient levels did not impair the NO3− uptake efficiency, maintaining similar NO3− content in the root and in the xylem sap. Second, leaf NO3− content was significantly reduced by the treatment of 5 mM Cl− in parallel with an increase in NO3− utilization and NUE. To verify whether Cl− nutrition reduces leaf NO3− accumulation by inducing its assimilation, we analysed the content of N forms and the activity of different enzymes and genes involved in N metabolism. Chloride supply increased transcript accumulation and activity of most enzymes involved in NO3− assimilation into amino acids, along with a greater accumulation of organic N (mostly proteins). A reduced glycine/serine ratio and a greater ammonium accumulation pointed to a higher activity of the photorespiration pathway in leaves of Cl−-treated plants. Chloride, in turn, promoted higher transcript levels of genes encoding enzymes of the photorespiration pathway. Accordingly, microscopy observations suggested strong interactions between different cellular organelles involved in photorespiration. Therefore, in this work we demonstrate for the first time that the greater NO3− utilization and NUE induced by beneficial Cl− nutrition is mainly due to the stimulation of NO3− assimilation and photorespiration, possibly favouring the production of ammonia, reductants and intermediates that optimize C-N re-utilization and plant growth. This work demonstrates new Cl− functions and remarks on its relevance as a potential tool to manipulate NUE in plants.